2021
DOI: 10.1080/14760584.2021.1999810
|View full text |Cite
|
Sign up to set email alerts
|

Identifying novel candidates and configurations for human helminth vaccines

Abstract: Introduction : Human infections with helminth worm parasites are extraordinarily prevalent across tropical and subtropical parts of the world, and control relies primarily on drugs that offer short-term suppression of infection. There is an urgent need for new vaccines that would confer long-lived immunity, protecting children in particular and minimizing community transmission. Areas covered : This article discusses the development of helminth vaccines, from the first … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 54 publications
0
10
0
Order By: Relevance
“…Helminth infections may lead to cognitive impairment [ 8 ], tissue damage [ 9 ], pregnancy complications [ 10 ], and numerous other symptoms and can sometimes be fatal [ 11 ]. The high prevalence, detrimental effects, and increasing drug resistance of helminths [ 12 , 13 ] have led to much research on developing vaccines [ 14 , 15 , 16 , 17 , 18 ]; however, despite promising results, there is still much to be done to achieve final success. Fully eradicating helminth infections may even in some aspects be controversial, since they may mitigate autoimmune diseases [ 19 , 20 , 21 ] and allergies [ 22 , 23 ] by dampening Th 1 and inducing Th 2 host immune responses [ 24 , 25 ].…”
Section: Helminthsmentioning
confidence: 99%
“…Helminth infections may lead to cognitive impairment [ 8 ], tissue damage [ 9 ], pregnancy complications [ 10 ], and numerous other symptoms and can sometimes be fatal [ 11 ]. The high prevalence, detrimental effects, and increasing drug resistance of helminths [ 12 , 13 ] have led to much research on developing vaccines [ 14 , 15 , 16 , 17 , 18 ]; however, despite promising results, there is still much to be done to achieve final success. Fully eradicating helminth infections may even in some aspects be controversial, since they may mitigate autoimmune diseases [ 19 , 20 , 21 ] and allergies [ 22 , 23 ] by dampening Th 1 and inducing Th 2 host immune responses [ 24 , 25 ].…”
Section: Helminthsmentioning
confidence: 99%
“…Large‐scale omics studies of EVs are essential to define molecular profiles that might be associated with specific biological roles. In fact, several studies have already shown that in vitro recovered EVs can have relevant immunomodulatory properties (Coakley et al., 2016 ; Drurey & Maizels, 2021 ; Hoffmann et al., 2020 ; Montaner et al., 2014 ; Sanchez‐Lopez et al., 2021 ; Tritten & Geary, 2018 ; Zakeri et al., 2018 ) and potentially participate to the drug resistance, diagnostic (Douanne et al., 2022 ; Khosravi et al., 2020 ; Mu et al., 2021 ) and disease prevention (Drurey et al., 2020 ; Khosravi et al., 2020 ; Maizels, 2021 ). Thus, characterization of EVs biomolecule composition should be a priority and availability in databases should be implemented.…”
Section: Specific Methodologies For Isolation Characterization and Pu...mentioning
confidence: 99%
“…Based on the concept that ML preventatives target larval stages of D. immitis and other filariae in the mammalian host by blocking the release of essential immunomodulating PDMs [ 30 34 ], a vaccine targeted against essential PDMs (assuming at least some are proteins) [ 35 ] could, in theory, elicit efficacy equivalent to the MLs, as the antibody response can develop over the roughly 2-month period of the life cycle in which the L4 stage develops. The difficulty of obtaining L4 stage D. immitis larvae has limited our ability to define essential PDMs as vaccine targets, although some PDMs from this parasite have been experimentally identified [ 36 38 ].…”
Section: Molecular Dialog Of the Host-parasite Interaction: Route To ...mentioning
confidence: 99%